Solution of the "Classical" Schrödinger equation for a driven symmetric triple well: A comparison with its classical counterpart. Issue 16 (17th May 2016) - Kar, Susmita; Kumar Chattaraj, Pratim
Abstract : The behavior of a driven symmetric triple well potential has been studied by developing an algorithm where the well‐established Bohmian mechanics and time‐dependent Fourier Grid Hamiltonian method are incorporated and the quantum theory of motion (QTM) phase space structures of the particle are constructed, both in "nonclassical" and "classical" limits. Comparison of QTM phase space structures with their classical analogues shows both similarity as well as dissimilarities. The temporal nature and the spatial symmetry of applied perturbation play crucial roles in having similar phase space structures. © 2016 Wiley Periodicals, Inc. Abstract : Triple well potential is a very good model for the study of the reaction dynamics of isomerization process among three species, as the three wells can represent the three species. Here, an algorithm for solving the "classical" Schrödinger equation using Bohmian mechanics and time‐dependent Fourier Grid Hamiltonian method has been developed and applied to a driven symmetric triple well system.